Robo-Blocks: Designing debugging abilities in a tangible programming system for early primary school children - Arnan Sipitakiat (2018)
Research on engaging young children in computer programming to develop high-level cognitive skills has suggested that debugging is among the most important actions leading to the development of logical thinking, problem solving, and social interaction skills. Although there have been a significant amount of studies done in this area, the debugging tools and techniques have been developed only as models and instructional methodologies outside of the tool itself. This work presents the design and analysis of debugging abilities embedded into a tangible programming system called Robo-Blocks. Students create a program by connecting physical command blocks, which then wirelessly controls the motion of a floor robot. Debugging is achieved by allowing children to run their program in a step-by-step manner and use passive objects to recognize and identify problems. Our evaluation with 52 children ages 8-9 has shown that (1) although tangible programming has the benefit of being exceptionally engaging to young children, early primary school children can quickly loose attention when no progress is made on a particular problem unless there are heuristics provided to help them move forward (2) Robo-Block's framework supplements the existing instructional methodologies used in the debugging process. Students showed significant increase in the ability to analyze problems and think of ways to correct them. © 2012 ACM.